Domestic Credit and Diversification of Manufactured Exports from Developing Countries. (14th December 2012) - Munemo, Jonathan
<x xml:space="preserve">Abstract</x> This article uses panel data to analyse the effect of domestic credit on the diversification of manufactured exports from developing countries. Given the evidence that export variety of manufactured goods affects productivity positively, the results imply that policy reforms that improve access to domestic credit for firms can raise productivity and hence economic growth in many poor countries. In addition, the results also show that building infrastructure and implementing reforms in governance that improve the quality of government regulations are important for encouraging diversification of manufactured export products in developing countries.